Traumatic experiences and cognitive profiles of schizophrenia cases influenced by the BDNF Val66met polymorphism. (January 2019) - Veras, André B.; Chao, Moses V.; Getz, Mara; Goetz, Raymond; Cheniaux, Elie; Lopes, Fabiana L.; Nardi, Antonio E.; Walsh-Messinger, Julie; Malaspina, Dolores; Kranz, Thorsten M.
Highlights: Early trauma has a significant influence on cognition. BDNF polymorphisms may determine stress response. Examinations of trauma should consider BDNF variants. BDNF Met carriers had worse perceptual organization, significantly associated with early traumas. Abstract: The association of early trauma exposure with current cognition was examined in a research series of 56 schizophrenia cases with respect to the BDNF Val66Met polymorphism (rs6265, Val66Val, Val66Met, Met66Met), as met allele carriers have reduced neurotrophic activity. The Perceptual Organization Index had a significant negative correlation with trauma exposures only in met carriers, including early physical abuse, general trauma after age 18 years, and physical abuse. Within the Val66Val subgroup, there were no significant correlations between WAIS indices and traumatic experiences.